Effect of masupirdine (SUVN‐502) on cognition in patients with moderate Alzheimer's disease: A randomized, double‐blind, phase 2, proof‐of‐concept study. Issue 1 (1st June 2022) - Nirogi, Ramakrishna; Ieni, John; Goyal, Vinod Kumar; Ravula, Jyothsna; Jetta, Satish; Shinde, Anil; Jayarajan, Pradeep; Benade, Vijay; Palacharla, Veera Raghava Chowdary; Dogiparti, Dhanunjay Kumar; Jasti, Venkat; Atri, Alireza; et al.
Abstract: Introduction: This study explored the efficacy and safety of a serotonin‐6 receptor antagonist, masupirdine, as adjunct treatment in patients with moderate Alzheimer's disease (AD) concomitantly treated with donepezil and memantine. Methods: The effects of masupirdine were evaluated in patients with moderate AD dementia on background treatment with donepezil and memantine. Five hundred thirty‐seven patients were expected to be randomized in a 1:1:1 ratio, using permuted blocked randomization. After a 2‐ to 4‐week screening period, the study consisted of a 26‐week double‐blind treatment period, and a 4‐week washout period. The primary efficacy measure was the 11‐item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS‐Cog 11). Secondary efficacy measures were Clinical Dementia Rating Scale–Sum of Boxes, Mini‐Mental State Examination, 23‐item Alzheimer's Disease Co‐operative Study Activities of Daily Living, and 12‐item Neuropsychiatric Inventory. Changes from baseline were analyzed using a mixed effects model for repeated measures (MMRM). A total of 564 patients were randomized to receive either daily masupirdine 50 mg (190 patients), masupirdine 100 mg (185 patients), or placebo (189 patients). The study is registered at ClinicalTrials.gov (NCT02580305). Results: The MMRM results showed statistically non‐significant treatment differences in change from baseline in ADAS‐Cog 11 scores at week 26, comparing each masupirdine dose arm to the placebo arm. No significant treatment effects were observed in the secondary evaluations. Discussion: Masupirdine was generally safe and well tolerated. Possible reasons for the observed trial results are discussed. Highlights: Masupirdine was evaluated in moderate Alzheimer's disease patients. First trial in class with background treatment of donepezil and memantine. Masupirdine was generally safe and well tolerated. Possible reasons for the observed trial results are discussed.